Clostridium butyricum Improves Rumen Fermentation and Growth Performance of Heat-Stressed Goats In Vitro and In Vivo - Liyuan Cai (MDPI AG, 2021)
This study aimed to evaluate the effects of Clostridium butyricum on rumen fermentation and the growth performance of heat-stressed goats. The in vitro fermentation was carried out using Clostridium butyricum supplement at 0% (CG), 0.025% (CB1), 0.05% (CB2), 0.10% (CB3), and 0.20% (CB4) of the dry matter (DM) weight of basal diet. Results showed that ruminal pH and the concentrations of ammonia nitrogen, total volatile fatty acids, acetic acid, propionic acid, as well as the acetic acid to propionic acid ratio were significantly increased (p < 0.05) in CB2 and CB3 compared with the CG group. Additionally, significant increases (p < 0.05) in the degradability of DM, neutral detergent fiber, and acid detergent fiber were observed in CB2 and CB3 compared with the CG group. For the in vivo study, 12 heat-stressed goats were divided equally into three groups: the control (HS1) was fed the basal diet, and groups HS2 and HS3 were fed with 0.05% and 0.10% Clostridium butyricum added to the basal diet, respectively. The experiment was designed as a 3 × 3 Latin square. Similar effects on rumen fermentation and digestibility parameters were obtained with 0.05% of Clostridium butyricum supplement compared to the in vitro study. Moreover, the dry matter intake and average daily gain were significantly increased (p < 0.05) in HS2 compared with other groups. These results indicated that an effective dose of Clostridium butyricum supplement (0.05%) could improve the rumen fermentation and growth performance of heat-stressed goats.